2020
DOI: 10.3390/microorganisms8030367
|View full text |Cite
|
Sign up to set email alerts
|

Siboglinidae Tubes as an Additional Niche for Microbial Communities in the Gulf of Cádiz—A Microscopical Appraisal

Abstract: Siboglinids were sampled from four mud volcanoes in the Gulf of Cádiz (El Cid MV, Bonjardim MV, Al Gacel MV, and Anastasya MV). These invertebrates are characteristic to cold seeps and are known to host chemosynthetic endosymbionts in a dedicated trophosome organ. However, little is known about their tube as a potential niche for other microorganisms. Analyses by scanning and transmission electron microscopy showed dense biofilms on the tube in Al Gacel MV and Anastasya MV specimens by prokaryotic cells. Metha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…Very low DO values of 0.64 mL•L −1 observed on deep-water mud volcanoes as Bonjardim in the GoC are closely to anoxia suggesting the intense activity of methane seeps (Figure 14D). If methane seeps are intense and/or undercurrents are weak in such deep waters, then low oxygen conditions prevail above seafloor and chemosynthesis-based habitats are only composed by colonies of Siboglinidae tubes [67]. However, in areas of methane seeps influenced by strong intermediate undercurrents (Figure 14D), co-occurrence of chemosynthesis-based and scleractinian-gorgonian aggregations has been detected as in this study and other MVs of the Gulf of Mexico [68].…”
Section: Dissolved Oxygen Concentrationssupporting
confidence: 66%
“…Very low DO values of 0.64 mL•L −1 observed on deep-water mud volcanoes as Bonjardim in the GoC are closely to anoxia suggesting the intense activity of methane seeps (Figure 14D). If methane seeps are intense and/or undercurrents are weak in such deep waters, then low oxygen conditions prevail above seafloor and chemosynthesis-based habitats are only composed by colonies of Siboglinidae tubes [67]. However, in areas of methane seeps influenced by strong intermediate undercurrents (Figure 14D), co-occurrence of chemosynthesis-based and scleractinian-gorgonian aggregations has been detected as in this study and other MVs of the Gulf of Mexico [68].…”
Section: Dissolved Oxygen Concentrationssupporting
confidence: 66%
“…o u r n a l P r e -p r o o f Journal Pre-proof There is plentiful evidence that active microbial activity takes place in the anterior part of siboglinid tubes at cold seeps. For instance, recent studies conducted at methane seeps recently identified Methylococcales and other methanotrophic bacteria as an abundant microbial group in the anterior portion of chitin tubes of siboglinids, including Escarpia southwardae(Medina-Silva et al, 2018;Rincón-Tomás et al, 2020). In addition to the primary sulphur-oxidizing symbionts present in the animal itself, the presence of abundant methanotrophic bacteria in the upper part of the tube of a Lamellibrachia species was also supported using methanotroph-specific molecular probes and sequencing of a subunit of methane monooxygenase(Duperron et al, 2009).…”
mentioning
confidence: 94%
“…[26]) and shrimp (e.g., Upogebia sp. [27]), have described important roles for the microbiome in host-environment interactions including metal resistance and sulfur cycling [2830]. Often the microenvironment of the tube or burrow created by these marine organisms is found to have a distinct microbiome from surrounding sediments [22,23,28,31].…”
Section: Introductionmentioning
confidence: 99%